The Implementation of Football Sports Coaching Management at Darul Huda Mayak Ponorogo Islamic Boarding School - Brian Kurniawan Widianto; Agus Kristiyanto; Hanik Liskustyawati (BIRCU, 2020)
Management is an activity process that is efficient, effective, and coordinated to maximize results. Sports management is a combination of management and sports science. Football achievement coaching is carried out at the Darul Huda Mayak Islamic Boarding School, Ponorogo, Indonesia. There is a decrease and an increase in achievement. The purpose of this study was to determine the implementation of football management, the causes of decline and increase in achievement and the obstacles faced from 2015-2020 by the Perasda Achievement Development Team, Darul Huda Mayak Islamic Boarding School. The method used in this research is descriptive qualitative. To find out how the management of football achievement coaching for Darul Huda Mayak, Ponorogo, Indonesia from 2015-2020. The results of this research team management are very good. In 2015-2020 there was no change in the management of the Persada football team. However, the decline in achievement occurred in 2017-2020 due to the weak ability of the Persada team in terms of penalties, besides that the Persada team's mainstay players had passed and the team split into two teams that took part in the National Santri League in 2018 and 2019.